Development of an Educational Board Game 'Tracing the Wild Boars Academy 13' to Enhance Problem-solving Skills Through Computational Thinking - Boonyoung, Thanyaporn; Jongkaijak, Sumalee; Phonphuttha, Haruethai; Sakdee, Patawee; Torsakul, Ob-Eau (Journal of Technical and Engineering Education, 2025)
This research aimed to: 1) Develop and test the efficiency of an educational board game set ‘Following the 13 Wild Boars Academy’ to promote problem-solving skills based on computational thinking principles, with an efficiency criterion of 80/80. 2) Compare students' learning achievement before and after using the educational board game. and 3) Study the satisfaction of using the "Following the 13 Wild Boars Academy" educational board game set. The sample group consisted of 35 fourth-grade students from Thanyasitthisin School, selected through simple random sampling. The research tools included 1) The "Following the 13 Wild Boars Academy" educational board game set, comprising digital media and a board game. 2) Quality assessment forms for digital media and educational board games. 3) Test to assess knowledge of computational thinking principles. 4) A problem-solving test based on computational thinking principles. and 5) A satisfaction questionnaire on the "Following the 13 Wild Boars Academy" educational board game set. Statistics used for data analysis included mean, standard deviation, and t-test. The results of the research showed that 1) The quality assessment of the "Following the 13 Wild Boars Academy" educational board game set by experts found that the digital media quality was at the highest level ( = 4.67, S.D. = 0.21), and the educational board game set quality was at the highest level ( = 4.73, S.D. = 0.28). The efficiency was 82.57/83.29, which is higher than the 80/80 criterion. 2) The comparison of learning achievement before and after using the "Following the 13 Wild Boars Academy" educational board game set, using t-test, found that the mean post-test score was significantly higher than the pre-test score at the 0.05 statistical level. 3) The students' satisfaction assessment of the educational board game was at the highest level ( = 4.61, S.D. = 0.57).